Barriers and enablers on the adoption of digital payments among retail consumers in Tacloban City - Eloy, Kristine Zaine C.; Labada, Mikee Ellaine C.; Mancol, Shaina Marie R.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2024)
The purpose of this study is to investigate the barriers and enablers on the adoption of digital payments among retail consumers in Tacloban City. The research employs a quantitative approach, utilizing a randomized cross-sectional survey design, and a survey was distributed online to collect data 123 participants responded to the survey. Both snowball and purposive sampling techniques were used. The study's objectives include assessing demographic characteristics, determining perceptions and behaviors towards digital payments, and analyzing prevalent consumer behavior patterns and preferences related to digital payment methods Results are analyzed using descriptive, correlation, ANOVA, and regression analysis. The findings reveal various relationships between different factors and their impact on the adoption of digital payments, emphasizing the significance of consumer motivation and user experience in shaping attitudes towards digital payments. The study also highlights the importance of addressing barriers such as limited access to smartphones and the internet, resistance to change, and security concerns in promoting the adoption of digital payments among retail consumers. The research provides valuable insights into the factors influencing the adoption of digital payments and offers recommendations for influencing consumer adoption, thereby providing guidance for stakeholders in promoting the effective use of digital payments in retail settings. The study concludes by emphasizing the need for targeted interventions to address barriers and enhance enablers for the widespread adoption of digital payments in retail transactions.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Digital payments -- Tacloban City; Adoption of digital payments -- Retail consumers -- Tacloban City; Digital payments; Adoption; Retail consumers; Behavior patterns; Preferences; Perceptions